Decoding of QAM signals over fading channels - Thet Thet Moe Zaw (Nanyang Technological University, 2021)
The quadrature amplitude modulation (QAM) is an important modulation technique that is currently used in the communication systems due to its efficient usage of power and bandwidth. One of the variations of the QAM signal is rotated QAM which the constellation rotates with reference to the In-phase and Quadrature axis. This study will include the simulation of rotated QAM and conventional QAM over the Rayleigh fading channel and Rician fading channel, as well as the bit-error rate (BER) performance of the signal. The purpose of this final year project report is to document the experience and knowledge gained and the result of the project that has been done in the final year of study. This report documents the study of the QAM modulation system and its BER performance via simulation using Matlab. The report will start with a brief background information of QAM as well as some of the features used in the project. Following that the simulation results and the conclusion on the project. The simulation results showed that the type of noise in the communication channels can affect the efficiency of the modulation scheme. As compared to the simple QAM modulation technique, rotated QAM seems to be more efficient. It has also shown that the angle of rotation of the rotated QAM has no effect on the BER performance. It is also concluded that QAM technique performs better in case of Rician fading channel as the bit-error rate is significantly lower than that of the Rayleigh fading channel.